Customized composite intervertebral disc scaffolds by integrated 3D bioprinting for therapeutic implantation. (August 2021) - Wu, Dongwei; Tan, Jianwang; Yao, Lingyun; Tian, Jinhuan; Luo, Binghong; Li, Lihua; Zhou, Changren; Lu, Lu
Highlights: Customized intervertebral disc construct was developed for therapeutic implantation. Simulating annulus fibrosus and nucleus pulposus structures of native disc. Composite hydrogel supported cell survival and extracellular matrix deposition. Maintaining disc height; disc repair effect equivalent to that of the reimplant disc. Abstract: In the past few years, tissue-engineered total disc replacement (TE-TDR) as a possible strategy to repair or regenerate intervertebral disc (IVD) has attracted considerable attention. However, to construct a patient-specific cell-based IVD scaffold with appropriate mechanical properties is still a challenge. The objective of this work is to develop stem cell-laden scaffolds mimicking the structure of native IVD. For this, an integrated 3D bioprinting system was used to combine polylactic acid and a double-network hydrogel to fabricate 3D biodegradable scaffolds with tailored properties. The mechanical performances, degradation behaviors and biocompatibility in vitro, as well as regeneration effect in rat caudal spine have been investigated. And the results demonstrate the feasibility of cell-laden IVD scaffolds by integrated 3D bioprinting. The developed IVD scaffolds can maintain the disc space and produce new extracellular matrix. It also proves that the TE-TDR strategy may provide a promising treatment for clinical applications.